ANALISIS DAN PENGATURAN TERHADAP TINDAK PIDANA PENCUCIAN UANG SEBAGAI KEJAHATAN KEUANGAN NASIONAL - SylviaNabila; Syaidah, Siti; Hosnah, Asmak Ul (Jurnal De Jure Muhammadiyah Cirebon, 2023)
The journal provides an explanation of the Analysis and Regulation of the Crime of Money Theft as a National Financial Crime. This journal was created with the aim of providing learning about the definition of the crime of money laundering, the money laundering process and the methods commonly used by money launderers. In this journal, provisions will also be discussed that money laundering criminal law. The problem of money laundering criminal acts is not only related to the laws in force in Indonesia but also related to national financial and economic problems. The method used in writing this journal is a normative juridicial approach method which is a comprehensive analysis of legal sources, primary and guided by legal provisions. Keywords: Legal Regulation, Money Laundering and Criminal Law